Versunkene Landschaften im Nordfriesischen Watt – Das aktuelle RUNGHOLT-Projekt zur Erforschung von Kulturspuren - Blankenfeldt, Ruth; Klooss, Stefanie; Hadler, Hanna; Majchczack, Bente Sven; Wilken, Dennis; Bienen-Scholt, Dirk (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
The North Frisian Wadden Sea is regarded as an important natural area and is now protected as a national park and a UNESCO World Heritage Site. At the same time, it is a relic of a submerged cultural landscape. Environmental influences, extreme weather conditions but also dyke construction and artificial land reclamation have constantly changed the region over the past millennia. While some areas could be regained after a devastating flood, other parts sank into the sea for ever. Remains of the lost terps and their agricultural land are preserved under the present-day surface of the Wadden Sea. An interdisciplinary, partly DFG-funded research project is addressing the systematic investigation of selected areas in the North Frisian Wadden Sea. Largescale non-invasive methods of geophysics together with analyses of aerial photographs and drone photography are combined with targeted geoarchaeological and archaeological investigations. A defined working area is located near the present-day Hallig Südfall, where the trading centre of Rungholt, which sank on 16 January 1362, is assumed to have been located. Here, for the first time, the path of a medieval dyke, terps, and drainage ditches could be reconstructed, and various locations of tide gates identified. Hallig Hooge and the surrounding tidal flats form another area of investigation. A large number of submerged settlement 60 areas as well as new insights into the extent and organisation of medieval salt peat quarrying are the focus of the current investigations here.